Ответы и объяснения

  • Участник Знаний
2013-05-03T11:23:50+04:00

cos4x-cos3x=0

-2sin(7x/2)*sin(x/2)=0

получим 2 случая

 

1) sin(7x/2)=0

7x/2=pik

x=2pik/7, k∈Z

 

2) sin(x/2)=0

x/2=pik

x=2pik, k∈Z

 

2.

sin3x-cos5x=0

cos 5x - sin 3x = 0
cos 5x + cos(pi/2 - 3x) = 0
Превращаем по формуле в произведение
2 cos 0,5(pi/2 + 2x) cos 0,5(8x - pi/2) = 0
Произведение равно 0, если какой-либо член равен 0
1) cos 0,5(pi/2 + 2x)  = 0
0,5(pi/2 + 2x)  = pi/2  + pi m
pi/2 + 2x = pi + 2 pi m
2x = pi/2 + 2 pi m
x = pi/4 + pi m


2) cos 0,5(8x - pi/2) = 0
0,5(8x - pi/2) = pi/2 + pi m
8x - pi/2 = pi + 2pi m
8x = 3 pi/2 + 2 pi m
x = 3 pi/16  + pi m/4